Berry Characterisation of cv Shiraz According to Position on the Rachis - Pisciotta, A.; di Lorenzo, R.; Barbagallo, M.G.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2016)
In this study, characterisation of the physical and compositional parameters of berries located in different positions on the rachis of Shiraz/R99 bunches was done. Berries were divided according to position on the rachis (apical, median and basal) and berry weight, resulting in four berry weight classes, averaging 0.86 g, 1.29 g, 1.74 g and 2.26 g and 0.74, 1.18, 1.59 and 2.09 cm3, respectively. The berries were analysed individually. The fresh weight of the berries comprised approximately 4% seeds, 20% skin and 76% flesh. Different percentage distributions were found for each class of berry weight and according to position on the rachis. From the top to the bottom rachis position, an increase in skin proportion value and a decrease in flesh and seed proportion value occurred. Skins decreased and flesh increased in proportion from the smallest to the largest berry size. The seed maintained a relatively stable proportion, irrespective of berry size. Larger berries had more flesh compared to skin than smaller berries. A higher level of soluble solids occurred in the shoulder to middle bunch area (28.7 °B and 28.6 °B, respectively) than in the bottom area (27.6 °B). It is extremely difficult to obtain uniform berry size and composition under field conditions. Continuous efforts are required to reduce variation and the potential negative impact on wine quality and consistency of wine style.